PENGEMBANGAN E-MODUL BERBASIS FLIPBOOK PADA MATERI TEKNIK DASAR PASSING DAN DRIBBLING BOLA BASKET - Hidayat, Wahyu; Suwiwa, I Gede; Mashuri, Hendra (Universitas Pendidikan Ganesha, 2023)
This research developed a flipbook-based e-module on the basic techniques of basketball passing and dribbling for 8th-grade students at SMP Negeri 1 Sawan. The study designed, measured validity, and analyzed participant responses to the e-module. The ADDIE development method was utilized with validation from subject matter experts, design experts, media experts, field practice tests, and individual trials. The results of feedback from teachers and students indicated a positive response level in various trials. The Physical Education teacher's response reached 92% with suggestions to improve color quality and cartoon images. The individual trial response reached 76% with feedback to enhance image sharpness. The small group trial response reached 85% with recommendations to improve image sharpness and transition animations. The large group trial response reached 80% with suggestions to enhance text clarity. Overall, the flipbook e-module received positive feedback from both teachers and students, indicating the potential to enhance the learning experience, although some improvement recommendations were provided.